Analisis Ketrampilan Gerak Badminton dengan Media Pembelajaran Virtual Reality (VR) pada Mahasiswa - Alexander, Bimo; Kustiawan, Andri Arif; Zulham (SPRINTER: Jurnal Ilmu Olahraga, 2025)
This study aims to analyze the effect of Virtual Reality (VR) learning media on Badminton motor skills in university students. Virtual Reality (VR) is considered a motor learning innovation that can simulate immersive game situations, thereby improving the quality of visual stimuli, kinesthetics, and motor decisions. The study design used a quasi-experimental pretest-posttest model on 30 students participating in the Badminton Student Activity Unit at the University. The assessment instrument included serve, forehand, backhand, and smash tests. The results showed a significant increase in the average motor skill score between before and after the VR intervention, with an average increase of 22.4%. Statistical analysis showed a p value <0.05, which means that VR media is effective in improving Badminton motor skills. These findings indicate that VR is feasible to be implemented as a technology-based motor learning innovation in universities. This study contributes to the development of physical education technology and offers an alternative approach in Badminton learning.